HYDROGEOLOGICAL STUDY TO SUPPORT SIGANDUL BRIDGE CONSTRUCTION AT PARAKAN, TEMANGGUNG, CENTRAL JAVA - Utomo, Edi prasetyo; Purwoarminta, Ananta (Teknologi Indonesia, 2015)
The plan of making bridge on the Sigandul river in Parakan, Temanggung regency is to improve the quality access roads in the Province of Central Java. The first step was to make the construction of the bridge pillars as the foundation of the bridge. For that purpose it was done drilling with planning a depth of 18 m, but at a depth of 12 m there was out of groundwater in a large discharge. This large groundwater discharge has disturbed the bridge construction process. The aim of this research is to analyze the causes of groundwater discharge and to provide a recommendation on counter measure of disturbance in the process of bridges construction based upon the hydrogeological condition. The methods used in this research were conducting a geological observation on ground surface and geoelectrical measurement with a dipole-dipole electrode arrangement. The results showed that the subsurface of research area is the site of groundwater accumulation and steep slope of its surrounding makes the groundwater came out with high pressure. Discharge rate of groundwater outflow in the area was 91.42 liters per second. Based on these conditions, it is recommended that the process of making a bridge construction should be done by first reducing the groundwater pressure or otherwise moving the foot of bridge the east side.